2002
DOI: 10.1105/tpc.005777
|View full text |Cite
|
Sign up to set email alerts
|

Host DNA Replication Is Induced by Geminivirus Infection of Differentiated Plant Cells

Abstract: The geminivirus Tomato golden mosaic virus (TGMV) replicates in differentiated plant cells using host DNA synthesis machinery. We used 5-bromo-2-deoxyuridine (BrdU) incorporation to examine DNA synthesis directly in infected Nicotiana benthamiana plants to determine if viral reprogramming of host replication controls had an impact on host DNA replication. Immunoblot analysis revealed that up to 17-fold more BrdU was incorporated into chromosomal DNA of TGMV-infected versus mock-infected, similarly treated heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 53 publications
4
41
0
1
Order By: Relevance
“…Similar findings were reported for S. cerevisiae, where DNA A of mung bean yellow mosaic India virus could replace the yeast autonomously replicating sequence in plasmid YCp50 and drive a geminivirus Rep-dependent replication of the respec- (55) observed that besides viral DNA, host plant DNA replication also was induced by TGMV infection and suggested that this might lead to endoreduplication. A recent study (6) found that genes that are necessary for a replication-competent environment tended to be upregulated during cabbage leaf curl virus infection, whereas genes coupled to mitosis tended to be downregulated.…”
Section: Resultssupporting
confidence: 82%
“…Similar findings were reported for S. cerevisiae, where DNA A of mung bean yellow mosaic India virus could replace the yeast autonomously replicating sequence in plasmid YCp50 and drive a geminivirus Rep-dependent replication of the respec- (55) observed that besides viral DNA, host plant DNA replication also was induced by TGMV infection and suggested that this might lead to endoreduplication. A recent study (6) found that genes that are necessary for a replication-competent environment tended to be upregulated during cabbage leaf curl virus infection, whereas genes coupled to mitosis tended to be downregulated.…”
Section: Resultssupporting
confidence: 82%
“…2, 5, and 6). Previous studies demonstrated that genetic changes, such as up-regulation of DNA replication machinery, are cell autonomous in geminivirus infections (Nagar et al, 2002), but more recent studies using microarrays (Ascencio-Ibañ ez et al, 2008) show that genes in pathogen response pathways that are regulated by diffusible compounds are also up-regulated. The GFP experiments demonstrated that only cells in the vascular tissue become infected, suggesting that genes expressed only in the mesophyll, epidermal, and other tissues may be more straightforward to analyze by VIGS.…”
Section: Discussionmentioning
confidence: 99%
“…Geminiviruses modify differentiation and cell cycle controls in mature leaf cells to induce replication of host chromosomal DNA as well as their own genomes (Nagar et al, 2002). They also dramatically change the transcriptome (J. T. Ascencio-Ibañ ez and L. HanleyBowdoin, unpublished data) and presumably the proteome of infected tissues.…”
Section: Discussionmentioning
confidence: 99%
“…AL1 interacts with the host pRBR to induce the expression of DNA replication machinery and cause mature plant cells to reenter the S phase of cell cycle (Ach et al, 1997;Kong et al, 2000;Nagar et al, 2002). Because GRIK1 and GRIK2 also interact with AL1, we asked if their expression is developmentally regulated, suggestive of intrinsic functions associated with DNA synthesis or differentiation.…”
Section: Grik1 and Grik2 Expression Is Regulated During Plant Developmentioning
confidence: 99%